Penerapan Manajemen Jalan Nafas pada Pasien Asma Bronkhial di Ruangan IGD RSUD Labuang Baji Makassar - Rezky Nur Inayah; Akbar Asfar; Wan Sulastri Emin (As-Syirkah: Islamic Economic & Financial Journal, 2025)
The condition Leiomyoma of the uterus, also known as uterine myoma or uterine fibroid, is a benign tumor of the uterus and represents the most common type of case.The aim of this scientific paper is to understand the application of airway management in patients with bronchial asthma in the Emergency Room (ER) of Labuang Baji Regional General Hospital, Makassar.This scientific paper employs observational methods regarding airway management procedures, specifically effective coughing exercises, and uses a descriptive approach based on case studies and the nursing process.In this scientific paper, it was found that after assessment and the provision of nursing interventions over a period of 2 hours (1x2 hours), bronchial asthma was managed effectively as reflected in the results of the scientific paper and the nursing care provided.It can be concluded that the nursing diagnosis for the patient with bronchial asthma involved effective coughing exercises conducted in the ER of Labuang Baji Regional General Hospital, Makassar. The nursing care actions provided were in accordance with the interventions outlined in the 3S book (SDKI, SLKI, SIKI).